'Obviously it's worth it': The Value of being a Canadian Student Athlete in the U.S.A. (2010) - ,
Abstract : Each year, young, elite Canadian athletes travel south to attend American colleges and universities, funded in part by athletic scholarships. These 'student athletes' leave their home country to pursue opportunities they believe are only available in the U.S. The demands made on their time, finances, and personal wellbeing can be staggering. Yet for those who become student athletes, the value of the experience tends to be unquestionably identified as being 'worth it'. In this paper, I explore how this exhortation, repeated so readily by the individuals I interviewed during fieldwork in the U.S., reflects a complicated set of beliefs. This deceptively simple statement provides an entry point for understanding what Canadian student athletes find valuable about their experience and how they believe it affords them a degree of personal distinction that would have been impossible had they stayed in Canada.